Anomalous Psychedelic Experiences: At the Neurochemical Juncture of the Humanistic and Parapsychological. (March 2022) - Luke, David
This article explores the nature of psychedelically induced anomalous experiences for what they reveal regarding the nature of "expanded consciousness" and its implications for humanistic and transpersonal psychology, parapsychology, and the psychology and underlying neuroscience of such experiences. Taking a multidisciplinary approach, this essay reviews the nature of 10 transpersonal or parapsychological experiences that commonly occur spontaneously and in relation to the use of psychedelic substances, namely synesthesia, extradimensional percepts, out-of-body experiences, near-death experiences, entity encounters, alien abduction, sleep paralysis, interspecies communication, possession, and psi (telepathy, precognition, and clairvoyance and psychokinesis).